Scaffold vaccination for prevention of orthopedic device infection - Alexander M. Tatara; Shanda Lightbown; Shawn Kang; Wei-Hung Jung; Hamza Ijaz; Jean C. Lee; Sandra B. Nelson; Michael Super; David J. Mooney (Proceedings of the National Academy of Sciences, 2025)
Staphylococcus aureus is the leading cause of global bacterial mortality. While S. aureus can cause a variety of diseases, orthopedic device infections are particularly challenging due to the need for additional surgeries with associated morbidity. Conventional vaccine technology has failed to prevent S. aureus orthopedic device infection in animal models and clinical trials. In this study, injectable scaffold vaccines are presented as a modality to augment host immunity and mitigate orthopedic device infection. These scaffold vaccines increased cytokine production, antigen-specific cell-mediated immune responses, and humoral responses. When loaded with a pool of antigens collected via an engineered human opsonin, these scaffold vaccines decreased the bacterial burden against methicillin-susceptible and methicillin-resistant S. aureus (MRSA) strains in a murine model of orthopedic device infection. Scaffold vaccination was ~100× more effective in decreasing S. aureus burden compared to prior published immunotherapy attempts in murine models of orthopedic device infection. Scaffold vaccination was also effective when using a monovalent protein-based antigen. Scaffold vaccination is an alternative strategy to facilitate more robust immunity in scenarios where conventional bolus vaccines have not been effective.